Preparation method and application of composite catalyst for synthesizing 1, 2-pentanediol through furfuryl alcohol hydrogenation

By using the Pd-Ru-CeO2-La2O3/Al2O3 composite catalyst, the problems of poor selectivity, insufficient stability and high cost of preparing 1,2-pentanediol catalysts for hydrogenation of furfuryl alcohol were solved, and efficient, stable and economical preparation of 1,2-pentanediol was achieved.

CN119701947AActive Publication Date: 2025-03-28SHANDONG UNIV OF TECH

Patent Information

Application Number
CN202510229467.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-03-28
Estimated Expiration
2045-02-28

AI Technical Summary

Technical Problem

The existing catalysts for preparing 1,2-pentanediol with hydrogenation of furfuryl alcohol have problems such as poor selectivity, insufficient stability and high cost, and need to react under high temperature and high pressure, resulting in an increase in by-products and a low yield of 1,2-pentanediol.

Method used

Using Pd-Ru-CeO2-La2O3/Al2O3 composite catalyst, a composite catalyst with high efficiency catalytic performance was prepared by spherical γ-Al2O3 as a support, combined with hydrothermal reaction and hydrogen reduction steps.

Benefits of technology

It improves the yield and selectivity of 1,2-pentanediol, reduces the occurrence of side reactions, extends the service life of the catalyst, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701947A_ABST
    Figure CN119701947A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of organic synthesis catalysts, and particularly relates to a preparation method and application of a composite catalyst for synthesizing 1, 2-pentanediol through furfuryl alcohol hydrogenation. The preparation method comprises the following steps: preparing cerium nitrate, lanthanum nitrate, urea, a surfactant and water into an aqueous solution, dipping spherical gamma-Al2O3, and then sequentially carrying out hydrothermal reaction, drying and roasting to obtain CeO2-La2O3 / Al2O3; the preparation method comprises the following steps: preparing palladium chloride, ruthenium chloride, hydrochloric acid and water into an acidic solution, dipping CeO2-La2O3 / Al2O3, drying, roasting and performing hydrogen reduction in sequence, thereby obtaining the composite catalyst Pd-Ru-CeO2-La2O3 / Al2O3. The composite catalyst can be applied to preparation of 1, 2-pentanediol through furfuryl alcohol hydrogenation. By preparing the composite catalyst, the defects of the existing catalyst in the aspects of selectivity, stability and cost are overcome.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of organic synthesis catalysts, and specifically relates to a preparation method and application of a composite catalyst for synthesizing 1,2-pentanediol by hydrogenation of furfuryl alcohol. Background Art

[0002] 1,2-Pentanediol is a straight-chain diol and an important intermediate for the synthesis of the fungicide propiconazole. It can be used as an excellent moisturizer and has an antiseptic effect, and can be used to formulate preservative-free products. 1,2-Pentanediol can also be used in various skin care products such as skin creams, eye creams, skin lotions, baby care products, and sunscreen products. The current methods for synthesizing 1,2-pentanediol mainly include the valeric acid method, the pentanol method, and the epoxidation hydrolysis method.

[0003] When petroleum is cracked to produce ethylene, a certain amount of byproduct C5 fraction is produced. The C5 fraction contains 1-pentene, which is one of the important raw materials for synthesizing 1,2-pentanediol. However, in the C5 fraction, compared with cyclopentadiene, isoprene and isoprene, the content of 1-pentene is relatively low. Therefore, the C5 fraction is more commonly used as fuel or used to produce petroleum resins and rubbers. Separating and purifying 1-pentene will increase costs. In addition, the complex synthesis process, many byproducts and high pollution also restrict the application of C5 fraction in the field of synthesizing 1,2-pentanediol. Therefore, production personnel hope to find a substitute for C5 fraction, which should have a wide source and lower cost. When using it to synthesize 1,2-pentanediol, it should have the advantages of mild reaction conditions, fewer byproducts and more environmental protection.

[0004] Under the action of a catalyst, furfuryl alcohol can be selectively hydrogenated to produce 1,2-pentanediol. Unlike the C5 fraction, furfuryl alcohol is mainly produced by hydrolyzing and fermenting biomass waste to produce furfural, which is then further hydrogenated. Biomass waste, such as corn cobs, bagasse or straw, has the advantages of wide sources, low cost and more environmental protection. The use of biomass waste to study the hydrogenation of furfuryl alcohol to produce high-value-added chemicals, especially 1,2-pentanediol, is of great significance to the industrial development of biomass furan compounds. Compared with other raw materials for the production of 1,2-pentanediol, furfuryl alcohol has a significant price advantage. In recent years, the research on the hydrogenation of furfuryl alcohol to produce 1,2-pentanediol has become a hot topic. The key to this process route is the development of suitable and efficient catalysts.

[0005] However, the existing Cu-Zn, Cu-Cr, Raney Cu or Raney Ni catalysts used in the hydrogenation of furfuryl alcohol to prepare 1,2-pentanediol have many shortcomings. For example, the selectivity of Cu-Zn catalyst is poor, and when used for the hydrogenation of furfuryl alcohol, a large amount of 2-methylfuran, 1,5-pentanediol and tetrahydrofurfuryl alcohol by-products will be produced; Cu-Cr has high environmental toxicity; and Raney Cu or Raney Ni have high preparation costs, insufficient stability, and are more likely to be deactivated by carbon sulfide deposition in biomass waste. In addition, the existing furfuryl alcohol hydrogenation to prepare 1,2-pentanediol requires reaction at high temperature and high pressure, which will also lead to an increase in reaction by-products, a low yield of 1,2-pentanediol and an increase in cost. At the same time, furfuryl alcohol contains unsaturated double bonds, which are easily polymerized at high temperatures to form oligomers, covering the active sites of the catalyst and reducing the activity of the catalyst.

[0006] Chinese patent CN104016831A discloses a method for preparing 1,2-pentanediol by hydrogenolysis of furfuryl alcohol. The method uses a catalyst to catalyze the hydrogenolysis of furfuryl alcohol. The catalyst is an Adams-type Pt(IV) oxide catalyst, an alumina (Al2O3)-supported ruthenium catalyst, or an activated carbon-supported ruthenium catalyst.

[0007] This patent has the following disadvantages: when the catalyst is regenerated, the combustion method is generally used to remove carbon deposits. The strength and thermal stability of activated carbon as a load carrier are relatively poor, which will affect the service life of the catalyst during regeneration. In addition, before modification and other measures are taken, single alumina is also prone to heat accumulation at high temperatures, causing local sintering, causing the metal active components to agglomerate, affecting dispersion. Summary of the invention

[0008] The purpose of the present invention is to provide a method for preparing a composite catalyst for synthesizing 1,2-pentanediol by hydrogenation of furfuryl alcohol, so as to solve the shortcomings of existing catalysts in terms of selectivity, stability and cost; the present invention also provides the application of the composite catalyst.

[0009] To achieve the above object, the technical solution adopted by the present invention is: The preparation method of the composite catalyst for synthesizing 1,2-pentanediol by hydrogenation of furfuryl alcohol according to the present invention, wherein the composite catalyst is Pd-Ru-CeO2-La2O3 / Al2O3, and the preparation method thereof comprises the following steps: (1) After drying the spherical γ-Al2O3, the water absorption rate α is measured; cerium nitrate, lanthanum nitrate, urea, a surfactant and water are prepared into an aqueous solution by ultrasonic dispersion, an equal volume of the aqueous solution is impregnated into the spherical γ-Al2O3, and CeO2-La2O3 / Al2O3 is obtained by hydrothermal reaction, drying and calcination in sequence; (2) The water absorption rate β of CeO2-La2O3 / Al2O3 is measured, and palladium chloride, ruthenium chloride, hydrochloric acid and water are prepared into an acidic solution by ultrasonic dispersion. An equal volume of the acidic solution is impregnated into CeO2-La2O3 / Al2O3, and then the mixture is dried, calcined and reduced with hydrogen to obtain Pd-Ru-CeO2-La2O3 / Al2O3.

[0010] in: In the step (1), the diameter of the spherical γ-Al2O3 is 1.5-3.5 mm; the drying temperature is 200-300°C, and the drying time is 1-2 hours; the mass ratio of the aqueous solution to the dried spherical γ-Al2O3 is 1.05α:1.

[0011] In the step (1), the molar ratio of cerium nitrate, lanthanum nitrate and urea is 1: (0.05-0.1): (3-10), the amount of surfactant used is 0.01-0.1% of the total weight of cerium nitrate and urea, the mass ratio of cerium nitrate and spherical γ-Al2O3 is (5-30): 100; the surfactant is one of hydroxymethyl cellulose, polyethylene glycol 400 or polyethylene glycol 600; and the ultrasonic dispersion time is 10-30 minutes.

[0012] In the step (1), the equal volume impregnation time is 20-30 hours; the hydrothermal reaction temperature is 120-180°C, and the hydrothermal reaction time is 24-48 hours; the drying temperature is 80-120°C, and the drying time is 5-10 hours; the roasting temperature is 350-600°C, and the roasting time is 1-2 hours.

[0013] In the step (2), the mass ratio of palladium element to ruthenium element in the acidic solution is 1:(0.25-2), the mass ratio of palladium element to spherical γ-Al2O3 in the acidic solution is (0.1-0.2):100; the pH value of the acidic solution is 2-4, and the ultrasonic dispersion time is 10-30min; the mass ratio of the acidic solution to CeO2-La2O3 / Al2O3 is 1.05β:1.

[0014] In the step (2), in the step (2), the equal volume impregnation time is 20-30 hours; the drying temperature is 80-100°C, and the drying time is 3-5 hours; the roasting temperature is 400-550°C, and the roasting time is 2-3 hours; the hydrogen reduction temperature is 100-300°C, and the hydrogen reduction time is 1-2 hours.

[0015] Application of the composite catalyst of the present invention: under the catalysis of Pd-Ru-CeO2-La2O3 / Al2O3, furfuryl alcohol and hydrogen are introduced to carry out hydrogenation reaction to obtain 1,2-pentanediol.

[0016] in: The molar ratio of furfuryl alcohol to hydrogen is 1:(10-100), and the flow rate of furfuryl alcohol is 0.51-3.08 g / min.

[0017] The Pd-Ru-CeO2-La2O3 / Al2O3 is loaded in a fixed bed, the pressure of the fixed bed is 0.8-1.5MPa, and the temperature of the fixed bed is controlled at 50-100°C.

[0018] Before the hydrogenation reaction, hydrogen is introduced into the activation bed: the activation temperature is 120-130°C, the activation pressure is 0.4-0.5MPa, and the activation time is 2.5-3.5h.

[0019] The volume space velocity of the hydrogenation reaction is 0.2-1.2h -1 .

[0020] The beneficial effects of the present invention are as follows: (1) CeO2 and La2O3 in Pd-Ru-CeO2-La2O3 / Al2O3 coordinate with Pd and Ru to reduce the probability of side reactions and increase the yield of the target product 1,2-pentanediol: CeO2 contains reversible Ce 3+ and Ce 4+ Redox pairs, in this oxidation-reduction atmosphere, make CeO2 reversibly release oxygen atoms and form a certain number of oxygen vacancies on the surface. On the one hand, it plays a role in maintaining the appropriate ratio of Pd / PdO. Pd in ​​the dissociation of H2 and PdO in the formation of hydroxyl groups can form a synergistic catalytic effect, minimize the existence time of unstable intermediate states, and thus effectively reduce the occurrence of side reactions. On the other hand, these oxygen vacancies have a tendency to accept oxygen atoms, which can reduce the adsorption activation energy of the -O- bond in furfuryl alcohol, promote the adsorption of furfuryl alcohol on the CeO2 surface, and reduce the probability of side reactions.

[0021] The addition of an appropriate amount of La2O3 can adjust the acidity and alkalinity of the catalyst, introduce a suitable proportion of basic sites on the catalyst surface, and dope La into the CeO2 lattice to induce the formation of more oxygen vacancies. At the same time, the basic sites of La2O3 and the acidic sites of CeO2 form an acid-base bifunctional surface, which optimizes the adsorption configuration of the reactants and prevents them from desorbing prematurely (for example, 2-methylfuran is generated due to premature desorption, because the hydroxyl group is removed before complete hydrogenation, leaving an unsaturated furan ring).

[0022] In the process of catalytic furfuryl alcohol hydrogenation, unsaturated hydrocarbons and mercaptan impurities in furfuryl alcohol are more likely to deposit carbon sulfides on the catalyst surface, leading to catalyst deactivation. The combustion method is generally used to remove carbon deposits and other deposits, but the γ-Al2O3 supported catalyst is easy to sinter at high temperatures (above 600°C), which will cause Pd and Ru to agglomerate, affect dispersion, and cover active sites. By adding La2O3, when the catalyst is regenerated, La2O3 will rearrange with part of the γ-Al2O3 to form a more heat-resistant LaAlO3-like structure, inhibiting the sintering phenomenon of the γ-Al2O3 catalyst during regeneration, facilitating high-temperature regeneration of the catalyst, and helping to extend the service life of the catalyst. In addition, La2O3 will form a composite crystal phase with Pd and Ru during calcination and hydrogen reduction, promoting the dispersion of the two active sites of Pd and Ru, and ensuring the catalytic activity of Pd and Ru.

[0023] In the present invention, Pd and Ru are the main active components: Pd and Ru form a bifunctional effect, that is, they catalyze different reaction steps respectively: Pd, as an efficient hydrogenation catalyst, can adsorb and activate H2 molecules, and PdO can promote the activated hydrogen to form a hydroxyl group (-OH) with an oxygen atom at the 2' site; and the addition of Ru can improve the selectivity for 1,2-pentanediol; the two synergistically catalyze furfuryl alcohol to prepare 1,2-pentanediol.

[0024] There is also a ligand effect between Pd and Ru. In Pd-Ru catalysts, the ligand effect is manifested as Ru changing the electronic structure and d orbital characteristics of Pd, thereby affecting Pd's adsorption and activation ability for hydrogen molecules. This effect can regulate the catalytic activity of Pd and enhance its selectivity. Experimental verification and spectral analysis have shown that the introduction of Ru through appropriate dosage and processing methods can promote the formation of 1,2-pentanediol.

[0025] (2) Since the main raw material for the preparation of furfuryl alcohol is biomass waste, furfuryl alcohol contains a small amount of unsaturated hydrocarbons, mercaptans and other substances. These substances are prone to form carbon sulfides and deposit on the catalyst surface over time during catalytic hydrogenation, resulting in catalyst deactivation. CeO2 and La2O3 in Pd-Ru-CeO2-La2O3 / Al2O3 coordinate with Pd and Ru to reduce carbon deposition and sulfide deposition, ensuring the activity of the catalyst for long-term use: Part of La2O3 enters the CeO2 lattice, which can inhibit the growth of CeO2 lattice and reduce the deposition sites of carbon sulfide. On the other hand, it can also improve the specific surface area of ​​the catalyst, ensure the dispersion of Pd and Ru, and increase the number of active sites. A larger specific surface area means that more sites participate in the reaction, reducing the possibility of carbon deposition on a single site, thereby maintaining the long-term activity of the catalyst. The oxygen vacancies in CeO2 also help to improve the redox ability of the catalyst, thereby reducing carbon deposition and sulfide deposition and maintaining the long-term activity of the catalyst. It has been verified by experiments that the yield of 1,2-pentanediol of the composite catalyst obtained by the present invention is still greater than 80% after 6 months of operation, indicating that its catalytic activity can maintain long-term stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a scanning electron microscope image of the composite catalyst Pd-Ru-CeO2-La2O3 / Al2O3 in Example 1. DETAILED DESCRIPTION

[0027] The present invention is specifically described and illustrated below in conjunction with embodiments.

[0028] Example 1 Measuring the water absorption rate α of spherical γ-Al2O3: Take 130g of spherical γ-Al2O3 with a diameter of 1.5-3.5mm, ultrasonically clean it, place it in a muffle furnace, heat it to 300℃, dry it for 60min, take it out, and cool it to room temperature. Accurately weigh 2.000g of the dried spherical γ-Al2O3 and place it in a flask. After vacuuming, pass distilled water until the spherical γ-Al2O3 is immersed. After standing for 15min, filter it. Place the soaked spherical γ-Al2O3 in a constant temperature operating box with a humidity of 90% and let it stand for 40min. Weigh the mass and calculate the water absorption rate α, which is 65.2%.

[0029] (1) Preparation of CeO2-La2O3 / Al2O3: 20 g of cerium nitrate, 1.99 g of lanthanum nitrate, 18.41 g of urea and 0.019 g of hydroxymethyl cellulose were weighed respectively, and the cerium nitrate, lanthanum nitrate, urea and hydroxymethyl cellulose were mixed with distilled water, and ultrasonically dispersed for 25 min to prepare a mixed solution A with a mass of 105α g. 100 g of dried spherical γ-Al2O3 was weighed and placed in a flask, and the spherical γ-Al2O3 was impregnated with equal volumes of the mixed solution A and the spherical γ-Al2O3 in a mass ratio of 1.05α:1, and allowed to stand for 20 h. Then, the mixture was put into an autoclave together for hydrothermal reaction at 150°C for 36 h, placed in a microwave oven, dried at 100°C for 8 h, and calcined in a muffle furnace at 350°C for 120 min to obtain CeO2-La2O3 / Al2O3.

[0030] (2) Preparation of composite catalyst Pd-Ru-CeO2-La2O3 / Al2O3: Accurately weigh 2.000 g of calcined CeO2-La2O3 / Al2O3, and measure the water absorption rate β of CeO2-La2O3 / Al2O3 according to the method for measuring the water absorption rate α in Example 1 to find that it is 63.6%. Weigh 0.265g of palladium chloride, 0.082g of ruthenium chloride, hydrochloric acid and distilled water, mix them, and ultrasonically disperse them for 10 minutes to prepare a mixed solution B with a mass of 105β grams. The pH of the mixed solution B is 4. Weigh 100g of calcined CeO2-La2O3 / Al2O3 and put it into a flask. According to the mass ratio of mixed solution B to CeO2-La2O3 / Al2O3 of 1.05β:1, equal volumes of CeO2-La2O3 / Al2O3 are impregnated, and the mixture is allowed to stand for 20 hours. Then, the mixture is put into a microwave oven together, dried at 95°C for 4 hours, and then calcined at 480°C for 160 minutes in a muffle furnace. Hydrogen is introduced at 250°C in a tubular furnace and reacted for 90 minutes to obtain a composite catalyst Pd-Ru-CeO2-La2O3 / Al2O3.

[0031] (3) Preparation of 1,2-pentanediol: Pd-Ru-CeO2-La2O3 / Al2O3 was loaded into a fixed bed reactor with a diameter of DN25 to form a bed with an effective loading height of 0.3m. The bed was provided with ceramic ring layers above and below, and each ceramic ring layer was 10cm high. The bed was replaced with nitrogen for 30min, and then replaced with hydrogen for 30min. The bed temperature was raised to 130°C and 0.5MPa with heat transfer oil, and hydrogen was passed for activation for 3h.

[0032] The furfuryl alcohol (density of furfuryl alcohol is 1.135 g / cm 3 ) continuously enters the fixed bed reactor at a rate of 0.51 g / min, and the hydrogen flow rate is controlled to enter the fixed bed at 0.104 g / min. The volume space velocity of the hydrogenation reaction is 0.2 h -1 The molar ratio of furfuryl alcohol to hydrogen is 1:10. The bed temperature is controlled at 50°C and the bed pressure is 1.5MPa by heat transfer oil. After 5 hours of reaction, the sample analysis shows that the content of 1,2-pentanediol is 73.28%, the content of 1,5-pentanediol is 11.65%, the content of tetrahydrofurfuryl alcohol is 14.16%, and the content of furfuryl alcohol is 0.89%. The fixed bed is operated continuously for one day, consuming a total of 734.4g of furfuryl alcohol. The reaction liquid is hydrogenated to obtain the reaction liquid, which is purified by distillation to obtain 1,2-pentanediol with a purity of 99.61%. The conversion rate of furfuryl alcohol is 99.03%, the selectivity of 1,2-pentanediol is 82.74%, and the yield is 81.94%. When the catalyst is used for 6 months, the catalyst activity does not decrease significantly.

[0033] Example 2 Measuring the water absorption rate α of spherical γ-Al2O3: Take 130g of spherical γ-Al2O3 with a diameter of 1.5-3.5mm, ultrasonically clean it, place it in a muffle furnace, heat it to 220℃, dry it for 120min, take it out, and cool it to room temperature. Accurately weigh 2.000g of the dried spherical γ-Al2O3 and place it in a flask. After vacuuming, pass distilled water until the spherical γ-Al2O3 is immersed. After standing for 15min, filter it. Place the soaked spherical γ-Al2O3 in a constant temperature operating box with a humidity of 90% and let it stand for 40min. Weigh the mass and calculate the water absorption rate α, which is 66.7%.

[0034] (1) Preparation of CeO2-La2O3 / Al2O3: 30 g of cerium nitrate, 1.495 g of lanthanum nitrate, 16.58 g of urea and 0.0466 g of polyethylene glycol 400 were weighed respectively, and the cerium nitrate, lanthanum nitrate, urea and polyethylene glycol 400 were mixed with distilled water, and ultrasonically dispersed for 30 min to prepare a mixed solution A with a mass of 105α g. 100 g of dried spherical γ-Al2O3 was weighed and placed in a flask, and the spherical γ-Al2O3 was impregnated with equal volumes of the mixed solution A and the spherical γ-Al2O3 in a mass ratio of 1.05α:1, and allowed to stand for 25 h. Then, the mixture was put into an autoclave together for hydrothermal reaction at 120°C for 48 h, placed in a microwave oven, dried at 120°C for 5 h, and calcined in a muffle furnace at 400°C for 95 min to obtain CeO2-La2O3 / Al2O3.

[0035] (2) Preparation of composite catalyst Pd-Ru-CeO2-La2O3 / Al2O3: Accurately weigh 2.000 g of calcined CeO2-La2O3 / Al2O3, and measure the water absorption rate β of CeO2-La2O3 / Al2O3 according to the method for measuring the water absorption rate α in Example 2 to find that it is 64.3%. Weigh 0.165g of palladium chloride, 0.41g of ruthenium chloride, hydrochloric acid and distilled water, mix them, and ultrasonically disperse them for 30 minutes to prepare a mixed solution B with a mass of 105β grams. The pH of the mixed solution B is 3. Weigh 100g of calcined CeO2-La2O3 / Al2O3 and put it into a flask. According to the mass ratio of mixed solution B to CeO2-La2O3 / Al2O3 of 1.05β:1, equal volumes of CeO2-La2O3 / Al2O3 are impregnated, and the mixture is allowed to stand for 30 hours. Then, the mixture is put into a microwave oven together, dried at 100°C for 3 hours, and then calcined at 550°C for 120 minutes in a muffle furnace. Hydrogen is introduced at 300°C in a tubular furnace and reacted for 60 minutes to obtain a composite catalyst Pd-Ru-CeO2-La2O3 / Al2O3.

[0036] (3) Preparation of 1,2-pentanediol: Pd-Ru-CeO2-La2O3 / Al2O3 was loaded into a fixed bed reactor with a diameter of DN25 to form a bed layer with an effective loading height of 0.3m. The bed layer was composed of ceramic ring layers above and below, and each ceramic ring layer was 10cm high. The bed layer was replaced with nitrogen for 30min, and then replaced with hydrogen for 30min. The bed temperature was raised to 125℃ and 0.4MPa with heat transfer oil, and hydrogen was passed for activation for 3.5h.

[0037] The furfuryl alcohol (density of furfuryl alcohol is 1.135 g / cm 3 ) continuously enters the fixed bed reactor at a rate of 1.54 g / min, and the hydrogen flow rate is controlled to enter the fixed bed at 0.63 g / min. The volume space velocity of the hydrogenation reaction is 0.6 h -1 , the molar ratio of furfuryl alcohol to hydrogen is 1:20, the bed temperature is controlled at 80℃ by heat transfer oil, the bed pressure is 1.0MPa, and the sample analysis after 5h of reaction: 1,2-pentanediol content is 75.68%, 1,5-pentanediol content is 18.86%, tetrahydrofurfuryl alcohol content is 4.87%, and furfuryl alcohol content is 0.22%. The fixed bed is operated continuously for one day, and a total of 2217.6g of furfuryl alcohol is consumed. The reaction liquid is hydrogenated to obtain furfuryl alcohol, and the reaction liquid is purified by distillation to obtain 1,2-pentanediol with a purity of 99.66%. The conversion rate of furfuryl alcohol is 99.78%, the selectivity of 1,2-pentanediol is 82.05%, and the yield is 81.87%. When the catalyst is used for 6 months, the catalyst activity does not decrease significantly.

[0038] Example 3 Measuring the water absorption rate α of spherical γ-Al2O3: Take 130g of spherical γ-Al2O3 with a diameter of 1.5-3.5mm, ultrasonically clean it, place it in a muffle furnace, heat it to 200℃, dry it for 100min, take it out, and cool it to room temperature. Accurately weigh 2.000g of the dried spherical γ-Al2O3 and place it in a flask. After vacuuming, pass distilled water until the spherical γ-Al2O3 is immersed. After standing for 15min, filter it. Place the soaked spherical γ-Al2O3 in a constant temperature operating box with a humidity of 90% and let it stand for 40min. Weigh the mass and calculate the water absorption rate α, which is 64.5%.

[0039] (1) Preparation of CeO2-La2O3 / Al2O3: 5 g of cerium nitrate, 0.39 g of lanthanum nitrate, 9.19 g of urea and 0.00142 g of polyethylene glycol 600 were weighed respectively, and the cerium nitrate, lanthanum nitrate, urea and polyethylene glycol 600 were mixed with distilled water, and ultrasonically dispersed for 10 min to prepare a mixed solution A with a mass of 105α g. 100 g of dried spherical γ-Al2O3 was weighed and placed in a flask, and the spherical γ-Al2O3 was impregnated with equal volumes of the mixed solution A and the spherical γ-Al2O3 in a mass ratio of 1.05α:1, and allowed to stand for 30 h. Then, the mixture was put into an autoclave for hydrothermal reaction at 180°C for 24 h, placed in a microwave oven, dried at 80°C for 10 h, and calcined in a muffle furnace at 600°C for 60 min to obtain CeO2-La2O3 / Al2O3.

[0040] (2) Preparation of composite catalyst Pd-Ru-CeO2-La2O3 / Al2O3: Accurately weigh 2.000 g of calcined CeO2-La2O3 / Al2O3, and measure the water absorption rate β of CeO2-La2O3 / Al2O3 according to the method for measuring the water absorption rate α in Example 1 to find that it is 63.1%. Weigh 0.33g of palladium chloride, 0.41g of ruthenium chloride, hydrochloric acid and distilled water, mix them, and ultrasonically disperse them for 20min to prepare a mixed solution B with a mass of 105β grams. The pH of the mixed solution B is 2. Weigh 100g of calcined CeO2-La2O3 / Al2O3 and put it into a flask. According to the mass ratio of mixed solution B to CeO2-La2O3 / Al2O3 of 1.05β:1, equal volumes of CeO2-La2O3 / Al2O3 are impregnated, and the mixture is allowed to stand for 25h. Then, the mixture is put into a microwave oven together, dried at 80℃ for 5h, and then calcined at 400℃ for 180min in a muffle furnace. Hydrogen is introduced at 100℃ in a tubular furnace and reacted for 120min to obtain a composite catalyst Pd-Ru-CeO2-La2O3 / Al2O3.

[0041] (3) Preparation of 1,2-pentanediol: Pd-Ru-CeO2-La2O3 / Al2O3 was loaded into a fixed bed reactor with a diameter of DN25 to form a bed layer with an effective loading height of 0.3m. The bed layer was composed of ceramic ring layers above and below, and the height of each ceramic ring layer was 10cm. The bed layer was replaced with nitrogen for 30min, and then replaced with hydrogen for 30min. The bed temperature was raised to 120℃ and 0.5MPa with heat transfer oil, and hydrogen was passed for activation for 2.5h.

[0042] The furfuryl alcohol (density of furfuryl alcohol is 1.135 g / cm 3 ) continuously enters the fixed bed reactor at a rate of 3.08 g / min, and the hydrogen flow rate is controlled to enter the fixed bed at 1.89 g / min. The volume space velocity of the hydrogenation reaction is 1.2 h-1 The molar ratio of furfuryl alcohol to hydrogen is 1:30. The bed temperature is controlled at 100°C by heat transfer oil, and the bed pressure is 0.8MPa. After 5 hours of reaction, the sample analysis shows that the content of 1,2-pentanediol is 71.26%, the content of 1,5-pentanediol is 23.58%, the content of tetrahydrofurfuryl alcohol is 4.25%, and the content of furfuryl alcohol is 0.18%. The fixed bed is operated continuously for one day, and a total of 4435.2g of furfuryl alcohol is consumed. The reaction liquid is hydrogenated to obtain the reaction liquid, which is purified by distillation to obtain 1,2-pentanediol with a purity of 99.72%. The conversion rate of furfuryl alcohol is 99.81%, the selectivity of 1,2-pentanediol is 82.33%, and the yield is 82.17%. When the catalyst is used for 6 months, the catalyst activity does not decrease significantly.

[0043] Comparative Example 1 CeO2-La2O3 / Al2O3 was replaced by activated carbon, and the remaining steps were the same as in Example 1 to prepare a Pd-Ru / AC catalyst.

[0044] The Pd-Ru / AC catalyst was used to prepare 1,2-pentanediol, and the operation steps were the same as in Example 1. The fixed bed was operated continuously for one day, and a total of 734.4 g of furfuryl alcohol was consumed. The reaction solution was purified by distillation to obtain 1,2-pentanediol with a purity of 99.56%. The conversion rate of furfuryl alcohol was 76.82%, the selectivity of 1,2-pentanediol was 50.69%, and the yield was 38.94%. When the catalyst was used for one month, the conversion rate of the raw material furfuryl alcohol dropped to 61.78%, and the catalyst activity dropped significantly.

[0045] Comparative Example 2 Without preparing an aqueous solution, the spherical γ-Al2O3 is only dried, and then an acidic solution is prepared and used to impregnate the dried spherical γ-Al2O3 with an equal volume. The remaining steps are the same as in Example 1 to obtain a Pd-Ru / Al2O3 catalyst.

[0046] The Pd-Ru / Al2O3 catalyst was used to prepare 1,2-pentanediol, and the operation steps were the same as those in Example 1. The fixed bed was operated continuously for one day, and a total of 734.4 g of furfuryl alcohol was consumed. The reaction solution was purified by distillation to obtain 1,2-pentanediol with a purity of 99.65%. The conversion rate of furfuryl alcohol was 95.18%, the selectivity of 1,2-pentanediol was 50.55%, and the yield was 48.11%. After one month of operation, the yield decreased to 44.37%.

[0047] Comparative Example 3 The palladium chloride and ruthenium chloride were replaced by copper nitrite, and the remaining steps were the same as those in Example 1. A Cu-CeO2-La2O3 / Al2O3 catalyst was obtained.

[0048] The Cu-CeO2-La2O3 / Al2O3 catalyst was used to prepare 1,2-pentanediol, and the operation steps were the same as in Example 1. The fixed bed was operated continuously for one day, and a total of 734.4 g of furfuryl alcohol was consumed. The reaction solution was purified by distillation to obtain 1,2-pentanediol with a purity of 99.63%. The conversion rate of furfuryl alcohol was 90.78%, the selectivity of 1,2-pentanediol was 56.77%, and the yield was 51.54%. After one month of operation, the yield decreased, and the conversion rate relative to furfuryl alcohol decreased to 80.27%, and the catalyst activity decreased significantly.

[0049] Comparative Example 4 The ruthenium chloride was replaced by palladium chloride, and the remaining steps were the same as those in Example 1. A Pd-CeO2-La2O3 / Al2O3 catalyst was obtained.

[0050] The Pd-CeO2-La2O3 / Al2O3 catalyst was used to prepare 1,2-pentanediol, and the operation steps were the same as in Example 1. The fixed bed was operated continuously for one day, and a total of 734.4 g of furfuryl alcohol was consumed. The reaction solution was purified by distillation to obtain 1,2-pentanediol with a purity of 99.58%. The conversion rate of furfuryl alcohol was 88.78%, the selectivity of 1,2-pentanediol was 51.80%, and the yield was 45.99%. After one month of operation, the conversion rate relative to furfuryl alcohol dropped to 65.72%, and the catalyst activity decreased significantly.

[0051] Comparative Example 5 The palladium chloride was replaced by ruthenium chloride, and the remaining steps were the same as those in Example 1. A Ru-CeO2-La2O3 / Al2O3 catalyst was obtained.

[0052] The Ru-CeO2-La2O3 / Al2O3 catalyst was used to prepare 1,2-pentanediol, and the operation steps were the same as those in Example 1. The fixed bed was operated continuously for one day, and a total of 734.4 g of furfuryl alcohol was consumed. The reaction solution was purified by distillation to obtain 1,2-pentanediol with a purity of 99.62%. The conversion rate of furfuryl alcohol was 98.78%, the selectivity of 1,2-pentanediol was 54.42%, and the yield was 53.76%. After one month of operation, the yield was 37.65%, and the yield decreased.

[0053] After 6 months of operation, 1,2-pentanediol was synthesized using the catalyst obtained in Example 1-3. The yield data of 1,2-pentanediol are as follows:

[0054] Evaluation of implementation effect: From the yield data of Examples 1-3 and Comparative Examples 1-5, it can be seen that the catalytic effect of the catalyst of Examples 1-3 still meets the use standard after 6 months of use, indicating that the catalyst has a good life and can be regenerated and used many times. However, the catalyst activity of the catalyst of Comparative Examples 1-5 decreased rapidly after 1 month of use, and no subsequent evaluation experiments were performed.

[0055] It can be seen from Comparative Examples 1-5 that Comparative Examples 1 and 2 cannot exert the synergistic effect of CeO2-La2O3; Comparative Examples 3, 4 and 5 cannot exert the synergistic effect of Pd-Ru. It can be seen that without CeO2-La2O3 or Pd-Ru, the use effect of the present invention cannot be achieved.

Claims

1. A method for preparing a composite catalyst for hydrogenating furfuryl alcohol to synthesize 1,2-pentanediol, characterized in that: The composite catalyst is Pd-Ru-CeO2-La2O3 / Al2O3, and its preparation method comprises the following steps: (1) After drying the spherical γ-Al2O3, the water absorption rate α is measured; cerium nitrate, lanthanum nitrate, urea, a surfactant and water are prepared into an aqueous solution by ultrasonic dispersion, an equal volume of the aqueous solution is impregnated into the spherical γ-Al2O3, and CeO2-La2O3 / Al2O3 is obtained by hydrothermal reaction, drying and calcination in sequence; (2) The water absorption rate β of CeO2-La2O3 / Al2O3 is measured, and palladium chloride, ruthenium chloride, hydrochloric acid and water are prepared into an acidic solution by ultrasonic dispersion. An equal volume of the acidic solution is impregnated into CeO2-La2O3 / Al2O3, and then the mixture is dried, calcined and reduced with hydrogen to obtain Pd-Ru-CeO2-La2O3 / Al2O3.

2. The method for preparing a composite catalyst for synthesizing 1,2-pentanediol by hydrogenation of furfuryl alcohol according to claim 1, characterized in that: In step (1), the diameter of the spherical γ-Al2O3 is 1.5-3.5 mm; the drying temperature is 200-300°C, and the drying time is 1-2 h; the mass ratio of the aqueous solution to the dried spherical γ-Al2O3 is 1.05α:

1.

3. The method for preparing a composite catalyst for synthesizing 1,2-pentanediol by hydrogenation of furfuryl alcohol according to claim 1, characterized in that: In step (1), the molar ratio of cerium nitrate, lanthanum nitrate and urea is 1: (0.05-0.1): (3-10), the amount of surfactant used is 0.01-0.1% of the total weight of cerium nitrate and urea, the mass ratio of cerium nitrate and spherical γ-Al2O3 is (5-30): 100; the surfactant is one of hydroxymethyl cellulose, polyethylene glycol 400 or polyethylene glycol 600; and the ultrasonic dispersion time is 10-30 minutes.

4. The method for preparing a composite catalyst for synthesizing 1,2-pentanediol by hydrogenation of furfuryl alcohol according to claim 1, characterized in that: In step (1), the equal volume impregnation time is 20-30 hours; the hydrothermal reaction temperature is 120-180°C, and the hydrothermal reaction time is 24-48 hours; the drying temperature is 80-120°C, and the drying time is 5-10 hours; the roasting temperature is 350-600°C, and the roasting time is 1-2 hours.

5. The method for preparing the composite catalyst for synthesizing 1,2-pentanediol by hydrogenation of furfuryl alcohol according to claim 1, characterized in that: In step (2), the mass ratio of palladium element to ruthenium element in the acidic solution is 1:(0.25-2), the mass ratio of palladium element to spherical γ-Al2O3 in the acidic solution is (0.1-0.2):100; the pH value of the acidic solution is 2-4, and the ultrasonic dispersion time is 10-30min; the mass ratio of the acidic solution to CeO2-La2O3 / Al2O3 is 1.05β:

1.

6. The method for preparing the composite catalyst for synthesizing 1,2-pentanediol by hydrogenation of furfuryl alcohol according to claim 1, characterized in that: In step (2), the equal volume impregnation time is 20-30 hours; the drying temperature is 80-100°C, and the drying time is 3-5 hours; the roasting temperature is 400-550°C, and the roasting time is 2-3 hours; the hydrogen reduction temperature is 100-300°C, and the hydrogen reduction time is 1-2 hours.

7. Use of a composite catalyst prepared by the method for preparing a composite catalyst for synthesizing 1,2-pentanediol by hydrogenation of furfuryl alcohol according to any one of claims 1 to 6, characterized in that: Under the catalysis of Pd-Ru-CeO2-La2O3 / Al2O3, furfuryl alcohol and hydrogen are introduced for hydrogenation reaction to obtain 1,2-pentanediol.

8. The use of the composite catalyst according to claim 7, characterized in that: The molar ratio of furfuryl alcohol to hydrogen is 1:(10-30).

9. The use of the composite catalyst according to claim 7, characterized in that: Pd-Ru-CeO2-La2O3 / Al2O3 is loaded in a fixed bed with a pressure of 0.8-1.5MPa and a temperature control of 50-100℃.

10. The use of the composite catalyst according to claim 7, characterized in that: The volume space velocity of hydrogenation reaction is 0.2-1.2h -1 .

Citation Information

Patent Citations

  • Hydrogenolysis of furfuryl alcohol to 1,2-pentanediol

    CN104016831A

  • Method for preparing 1,2-pentanediol by furfuryl alcohol liquid phase selectivity and hydrogenolysis

    CN104370702A

  • Catalyst for catalyzing furfural or furfuryl alcohol to prepare cyclopentanol through hydrogenation rearrangement and preparation method and application method thereof

    CN104998659A

  • Preparation method of tetrahydrofurfuryl alcohol

    CN109796427A

  • Compositions comprising 1,2-pentanediol

    CN112912051A

Cited By

  • Preparation method of 1, 2-pentanediol

    CN122146800A